Acoustical and thermal properties of lightweight coir fiber reinforced cements composites - Ahmad, Zuraida; Purwanto, Hadi; Sarifuddin, Norshahida; R. F. , Faezah; Y. , Farrah (2011)
Increasing attention has been paid on the creation of environmental friendly with higher performance type cement composite with a view to conserve energy and protecting environment. In this current work, the development of lightweight cement composites with use of agriculture waste, coir fiber, and biopolymer, egg albumen were described. Besides the mechanical and physical properties, work presented herein aim to explore the sound absorption and thermal performance of cement composites. Under optimum conditions, the CFRCC was fabricated via mixing, casting and curing. The fiber volume were substantially varied from 1 to 6 wt. %. The fabricated CFRCC were then subjected to impedance tube and thermal guarded hotplate to evaluate the sound absorption and thermal conductivity, respectively. The sound absorption coefficient (α) was found to increase with an increased in fiber volume and this effect is more prominent with higher sound frequencies. The addition of fiber lowers its thermal conductivity (λ) and it is found to be further reduced as the fiber content is increased. This result showed that CFRCC have potential for absorbing sound, while thermal conductivity is practically have lower thermal conductivity value compare to plain concrete